Multi-agency working. (Education in video, 2006)
Support staff at David Lister School in Hull are leading the way in multi-agency working. They['ve shown that the in-house team, comprising social workers, family assessors and a dedicated co-ordinator can meet even the most challenging cases at this tough inner city school. Max Roberts, a former headteacher in Hull, took on the responsibility of kick-starting and coordinating the project, which is called MAST. They meet every week with teachers to identify pupils with the most serious needs and then draw on the expertise of outside agencies such as the police, fire service and youth workers. Crucial to the success of MAST has been the development of these close working relationships. The team has proven its effectiveness by easing the pressure on teachers, enabling them to concentrate on teaching. Due to the achievements of MAST, the school has now been invited to take part in a pilot scheme to test common assessment, a new way for all agencies to work together.